BALANCING EXPECTATIONS: HARMONIZING CUSTOMER CONTROL WITH EMPLOYEE WELL-BEING FOR LONG-TERM SUCCESS (Contemporary Journal of Social Science Review, 2025)
An increasingly popular idea in management is "customer control," which describes the power consumers have on goods, services, and employees behavior. The dynamics between customer input, employee attitudes, and service delivery outcomes are the main subject of this study, which looks at how consumer control affects workers and organizational procedures. The study uses sentiment analysis to find organizational behaviors and emotional reactions in seven participants' semi-structured interviews. The results show that although customer control improves operational effectiveness, personalization, and service quality, it also poses problems for performance management, employee motivation, and mental health. For a business to succeed over the long term, it is essential to strike a balance between the advantages and disadvantages of customer control. This study contributes to the literature on value co-creation by providing managerial insights into the complexities of customer control and its implications for employee behavior. Future research should explore strategies for managing the long-term psychological and operational impacts of customer control.